2019
DOI: 10.1136/openhrt-2019-001067
|View full text |Cite
|
Sign up to set email alerts
|

Scar burden is an independent and incremental predictor of cardiac resynchronisation therapy response

Abstract: ObjectiveDetermine the prognostic impact of scar quantification (scar %) by cardiac magnetic resonance (CMR) in predicting heart failure admission, death and left ventricular (LV) function improvement following cardiac resynchronisation therapy (CRT), after controlling for the presence of left bundle branch block (LBBB), QRS duration (QRSd) and LV lead tip location and polarity.MethodsConsecutive patients who underwent CMR between 2002 and 2014 followed by CRT were included. The primary endpoint was death or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“… 4 Avoiding scarred areas pacing is critical since nonviable tissue can no longer be resynchronized. 5 In the present case, scar formation was evident around the left ventricle and right ventricle apex pacing sites. No studies have so far evaluated the importance of myocardial substrate and remodelling for RV lead placement.…”
supporting
confidence: 48%
“… 4 Avoiding scarred areas pacing is critical since nonviable tissue can no longer be resynchronized. 5 In the present case, scar formation was evident around the left ventricle and right ventricle apex pacing sites. No studies have so far evaluated the importance of myocardial substrate and remodelling for RV lead placement.…”
supporting
confidence: 48%
“…Despite this, nearly a third of patients treated with CRT enjoy no benefit. The burden of myocardial fibrosis is an important independent predictor of response to CRT [5] , with extensive LV myocardial scar contributing to impaired LV reverse remodelling. This may explain why individuals with underlying ischemic cardiomyopathy respond less frequently to CRT compared to individuals with non-ischemic cardiomyopathy [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, only two thirds of patients meeting guideline criteria for CRT implantation garner optimal benefits from this device therapy [4] . Furthermore, myocardial fibrosis and scar burden are principal factors that adversely affect the response from CRT at a substrate level [5] , [6] . Cardiac MRI is the reference standard for detecting and quantifying myocardial fibrosis and scar [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serge C. Harb et al have shown that nonresponders have a higher level of myocardial scar burden. Also, myocardial scar burden is an independent factor in predicting heart failure and death, and also in predicting ejection fraction recovery after CRT implantation (Figure 1) [17]. The higher level of myocardial scar burden regardless of the scar location in terms of affected segments is marked as a predictor of adverse outcomes.…”
Section: Myocardial Scar Burden As a Predictor Of Responsementioning
confidence: 98%